Gejolak dalam Harmoni - Mujiyono Mujiyono (Institut Seni Indonesia Yogyakarta, 2010)
Harmony in Frightening Natural Phenomenon. The main creation source is the aesthetic impressions of clouds and waves which implicitly express frightening, fearful, and scary passion. The objects of the creations are expressed in painting arts which tend to be expressionistic and abstract in style. The supporting sources of the creations are some paintings of Franz Kline, Willem de Kooning, Joan Mitchell, Anselm Kiefer, Piet Mondrian, and Ibrahim. The originality is emphasized in individual emotional expression. The methods of the creations begin with the exploration of ideas, improvisations, and creations which become one activity. The transformation of ideas into art products creates a subject matter which contains biomorphic forms from expressive brushing that is based on intuition and spontaneousness. The differences in the width of the brush, the stress of brushing, the level of painting thickness, and the color have become the supporting techniques. The results of the creation are the painting art products containing line configurations, organic forms, and coloring with the wild, free, uncontrolled, and ‘mleber’ effects. Keywords: Expressionistic abstract, art harmony, painting.